Journal of Electric Propulsion - Keidar, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Electric propulsion is a rapidly evolving area with wide applications to spacecraft, satellites, and probes. The Journal of Electric Propulsion aims to fill a gap in the current literature, with coverage from plasma physics and materials science to the engineering of novel electric propulsion systems. In the process, the journal provides a broad forum of expertise by bringing together researchers and scientists from both academia and industry with a wide range of backgrounds in fundamental and applied aerospace sciences. Potential topics include, but are not limited to: physics of electric propulsion plasma thrusters plasma plumes diagnostics and modeling related to electric propulsion material aspects system engineering and integration flight experiments laser and nuclear propulsion.
Keywords: Plasma (Ionized gases).; Outer space$1 (BExploration.s; Astronautics; Physics; Plasma Physics; Space Exploration and Astronautics; Applied and Technical Physics